Advantages of a slim vertical gas channel at high SiHCl3 concentrations for atmospheric pressure silicon epitaxial growth. (15th November 2018) - Irikura, Kenta; Muroi, Mitsuko; Yamada, Ayami; Matsuo, Miya; Habuka, Hitoshi; Ishida, Yuuki; Ikeda, Shin-Ichi; Hara, Shiro
Abstract: Effective process conditions to utilize a slim vertical silicon chemical vapour deposition reactor were studied. Based on a numerical analysis taking into account the gas flow, heat and species transport, particularly over a wide range of the trichlorosilane gas concentrations from 1% to 40% in ambient hydrogen, a heavy and cold gas was shown to quickly go downward to the hot wafer surface through the slim vertical gas channel. The gas phase near the wafer was sufficiently cooled to produce a cold wall thermal condition which enabled the trichlorosilane gas consumption only at the wafer surface, even in a non-axisymmetric and non-steady condition. The slow wafer rotation, less than 30 rpm, had a considerable effect, such as that increasing the gas phase temperature gradient for suppressing the gas phase reaction.